'It's not like the Germans to take something that wasn't theirs': Exploring issues of ownership and creative borrowing as a challenge for transnational format adaptation through Stromberg. (June 2018) - Schwind, Kai Hanno
At the time of its conception, the producers of Stromberg, the German adaptation of the British situation comedy The Office, were accused of copyright infringement. Based on exclusive data from qualitative interviews with the creative personnel, this article contributes to the previously under-theorised field of television comedy production studies in non-Anglophone contexts. Exploring the clash of standardised procedures on the global television market with traditional practices and a distinct production culture in Germany, it challenges established theorisations of television 'format' and argues for a more nuanced and case-specific understanding of how adaptation processes facilitate and stimulate creativity across borders.